Brodie's or Hummers' Method: Oxidation Conditions Determine the Structure of Graphene Oxide. Issue 38 (6th June 2019) - Feicht, Patrick; Biskupek, Johannes; Gorelik, Tatiana E.; Renner, Julian; Halbig, Christian E.; Maranska, Maria; Puchtler, Florian; Kaiser, Ute; Eigler, Siegfried
Abstract: Synthesis and studies of graphite oxide started more than 150 years ago and turned into a boom by the measurements of the outstanding physical properties of graphene. A series of preparation protocols emanated trying to optimize the synthesis of graphene oxide in order to obtain a less defective material, as source for graphene. However, over‐oxidation of the carbon framework hampered establishing structure‐property relationships. Here, the fact that two different synthetic methods for graphene oxide preparation lead to very similar types of graphene oxide with a preserved graphene lattice is demonstrated. Either sodium chlorate in nitric acid (similar to Brodie's method) or potassium permanganate in sulfuric acid (similar to Hummers' method) treatment are possible; however, reaction conditions must be controlled. With a preserved carbon lattice analytical differences between the samples relate to the altered on‐plane functionality. Consequently, terming preparation protocols "according to Brodie's/Hummers' method" is not sufficient. Abstract : Graphite oxidation by using either sodium chlorate or potassium permanganate leads in both cases to similar materials, which permits to demystify the synthesis methods of graphene oxide.